CECT and CT Perfusion Correlation with Pathological Differentiation of Pharyngeal and Laryngeal Cancers: Study from a Tertiary Care Center in Northeast India - Phukan, Himraj; Lynser, Donboklang; Daniala, Chhunthang; Raphael, Vandana; Harris, Caleb; Chakraborty, Suvamoy (Indian Journal of Radiology and Imaging, 2024)
Introduction Pharyngeal and laryngeal carcinomas, included under head and neck cancers, pose a significant challenge in India, accounting for around one-third of all cancer cases. Noninvasive techniques like contrast-enhanced computed tomography (CECT) and CT perfusion (CTp) can help explore the correlation between tumor differentiations, which can greatly benefit in the diagnosis, understanding of recurrence postintervention, and monitoring of the progress of the disease.Materials and Methods A hospital-based cross-sectional study was conducted for a duration of 18 months in a tertiary care center of northeast India with a sample of 40 patients. CECT and CTp were done and the variables were correlated with pathological differentiation of tumors.Results The mean age of the study population was 54 years. No statistically significant associations were noted between the age, size, margins, location, and T-staging of tumors with the pathological differentiation of tumors. However, significant association was found between the CTp parameters, namely blood flow (BF), blood volume, mean transit time, time to drain, and time to peak with respect to the pathological differentiation of tumors (p < 0.05).Conclusion The addition of CTp to conventional CT sequences in the evaluation of pharyngeal and laryngeal cancers offers significant benefits in understanding the tumor physiology and behavior.
Keywords: blood flow; blood volume; computed tomography perfusion; contrast-enhanced computed tomography; mean transit time; pharyngeal and laryngeal cancers; time to drain; time to peak